What Predicts Ongoing Nonsuicidal Self-Injury? - Kiekens, Glenn; Hasking, Penelope; Bruffaerts, R.; Claes, L.; Baetens, I.; Boyes, Mark; Mortier, P.; Demyttenaere, K.; Whitlock, J. (Lippincott Williams & Wilkins, 2017)
Although nonsuicidal self-injury (NSSI) peaks in adolescence, a significant proportion of young people continue to self-injure into emerging adulthood. Yet, little is known about factors prospectively associated with persistent NSSI. Using data from a 3-year longitudinal study (n = 1466), we compared 51 emerging adults (67.3% female; average age, 20.0 years) who continued to self-injure from adolescence and 50 emerging adults (83.7% female; average age, 20.3 years) who had ceased NSSI, on a broad range of psychosocial factors. More frequent NSSI, use of a greater number of methods, specific NSSI functions, academic and emotional distress, and lack of perceived emotion regulatory capability differentiated emerging adults who continued with NSSI and those who had ceased the behavior. Further, the relationships between social support, life satisfaction, and NSSI were mediated by perceived ability to regulate emotion. Findings from this study point to the role of personal belief in the ability to effectively regulate emotion in the cessation of NSSI. Future research directions and clinical implications are discussed.